PsycEXTRA Dataset 2010
DOI: 10.1037/e607492011-001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of short breaks on families with a disabled child: report one of the quantitative phase

Abstract: We would also like to thank members of the research policy steering group who reviewed the progress of the research and advised and commented on draft materials etc. It is our Policymakers and local authorities will also need to consider such a rebalancing beyond the provision of 'child' services, as many young disabled people move into adulthood whilst still living with their family carers. Such a transition point is often felt as catastrophic by families as an array of family supports, including short breaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The development of new practice has often taken the form of pilot or pathfinder initiatives and the independent evaluations of key programmes are still in the early stages or have yet to report (e.g. Jessiman and others, ; Welch and others, ). It is unlikely therefore that children and families in any numbers will have experienced the scale and type of benefits that the policies set out to deliver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of new practice has often taken the form of pilot or pathfinder initiatives and the independent evaluations of key programmes are still in the early stages or have yet to report (e.g. Jessiman and others, ; Welch and others, ). It is unlikely therefore that children and families in any numbers will have experienced the scale and type of benefits that the policies set out to deliver.…”
Section: Discussionmentioning
confidence: 99%
“…Gordon and others () reported that within the population of families with disabled children in Britain, the poorest 20 per cent often obtained fewer services than others. While more up‐to‐date research on the social patterning of service usage across the whole population of disabled children is lacking, a recent study found inequality in access to a key provision, short breaks, with families in more deprived circumstances tending to receive less support than those who were better off (Welch and others, ).…”
Section: Poverty and Deprivationmentioning
confidence: 99%